A 2-D transient numerical heat transfer model of the solar absorber plate to improve PV/T solar collector systems. (1st September 2017) - Paradis, Pierre-Luc; Rousse, Daniel R.; Lamarche, Louis; Nesreddine, Hakim
Highlights: A 2-D transient numerical model of a thermally enhanced solar absorber PV plate is proposed. The multi-physics model includes optical, electrical and heat conduction models. An experimental setup is especially designed to validate the model. A maximum discrepancy of less than 2 [°C] is obtained for the temperature. A maximum discrepancy of less than 7 [%] is obtained for the electric power. Abstract: This paper presents a genuine 2-D transient numerical model to evaluate the temperature field and the dependent electrical performances of different solar absorber plates. It can readily be adapted for solar thermal absorber plates, standard PV plates or thermally enhanced PV plates that can be used in PV/T solar collectors. The model can also be combined with the appropriate heat exchanger equations to simulate a complete solar collector. A simple optical model is combined with the well-known five parameters PV module electrical model and the 2-D heat conduction equation to compute the temperature field of the PV plate and the electrical power generated for every time step of the simulation. The resulting differential equation is solved through finite volume discretization using an implicit time discretization scheme. The model relies on widely available weather parameters such as total horizontal solar radiation, ambient temperature, wind speed, etc. Validation of the electrical model is first carried out in real outdoor weather conditions comparing simulated and measured electrical current. During this process, measured temperature of the plate and incident solar radiation are used as inputs. Then, the global multi-physic model is validated using a temperature measurement at a selected point and the measured electrical performances. In the multi-physic model, measurements of the incident solar radiation, air temperature, wind speed and relative humidity are used as inputs. The validation results for the temperature showed a maximum discrepancy of the numerical predictions with respect to the measurements of less than 2 [°C] and a discrepancy below 7 [%] for the electric power production both over a complete day of simulation.